Segmented growth of reactivated major bounding faults and their control on basin structures: Insights from the Nanpu Sag, Bohai Bay Basin, eastern China - Lou, Rui; Sun, Yong‐He; Tian, Wen‐Guang; Gao, Tian (Basin research, 2024)
A thorough insight into the initiation, segmentation, propagation and interaction of multitrend basin‐bounding faults is crucial to restoring the growth history of the faults and clarifying the fault growth pattern and its influence on the structures developed along the margin due to the growth of the basin‐bounding faults, but systematic studies on the individual influence of the evolution of each fault segment on the present structure are lacking. Based on 3D seismic data, the timing and growth of multitrend basin‐bounding faults were analysed using T‐z plots and throw backstripping, allowing us to determine the individual effects that each fault segment evolution exerteds on the present‐day configuration of the northern margin of the Nanpu Sag. The basin‐bounding fault is composed of the Xinanzhuang and Baigezhuang faults, and the Xinanzhuang fault comprises three linked segments with varying orientations (i.e., NE–SW, E–W, and NNE–SSW). In comparison, the Baigezhuang fault comprises only two linked NW–SE‐oriented fault segments. The evolution process can be divided into three stages. (1) During the early synrift I stage, namely, the isolated fault stage, five isolated multitrend basin‐bounding segments were active. (2) During the late synrift I stage, namely, the hard‐linkage stage, the five segments propagated laterally and linked with each other, behaving as a single fault. Meanwhile, the NE‐trending No. 5 Fault bifurcated upward from the basin‐bounding fault to accommodate local stress, and the NW‐trending Gaobei Fault deviated from the basin‐bounding fault controlled by local stresses induced by differential activities of the multitrend fault segments under the same far‐field stress. (3) During the synrift II to postrift linkage development stage, the extension orientation changed from NW–SE‐ to N–S, and additional displacement accumulated along the basin‐bounding fault without further lateral propagation. Newly formed E–W‐trending faults developed orthogonal to the extension orientation and linked with preexisting NE‐ or NW‐trending faults, forming a complex fault zone. In addition, influenced by the geometry of the basin‐bounding fault, the Laoyemiao Anticline formed by gravitational collapse under the dual action of a rollover anticline and transverse anticline. Furthermore, the evolution of the basin‐bounding faults played an important role in controlling the source‐to‐sink system, and the transition zone was the main provenance channel formed by the segmented growth of the faults. This study provides new insight into multitrend large fault evolution, and their impact on basin development provides a comprehensive explanation of the later structures developed in polyphase rifts. Related deformation of the hanging‐wall of XF1, XF2 and XF3 of the Nanpu Sag in three‐dimensional views (a–c) and the conceptual model (d–f). Branch lines are highlighted by bold lines.